The Effect of the Autoimmune Conditions on Pulpal and Periapical Disease Progression: A Narrative Review - AlGhaslan, Rakan Khalid; Alissa, Ibrahim Hamad; Alabdullateef, Khalid Saleh (Journal of Posthumanism, 2024)
Systemic conditions known as autoimmune diseases are typified by an abnormal immune response against self-antigens, which frequently results in tissue damage to multiple organs and chronic inflammation. These systemic immune dysregulations have the potential to greatly impact the pathophysiology and healing results of the periapical tissues and dental pulp. Patients with autoimmune diseases like systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), Sjögrens syndrome, and type 1 diabetes mellitus experience changes in their inflammatory response, which is essential in the onset and resolution of pulpal and periapical diseases. In addition to influencing the course of infection and inflammation, this compromised immunity also impacts the pulps and the periapical regions' ability to heal after endodontic treatment. Additionally, immunosuppressive therapies that are frequently recommended for autoimmune patients complicate dental care by postponing tissue repair and making patients more vulnerable to secondary infections. To better understand how autoimmune diseases affect the development course and resolution of pulpal and periapical pathologies, this narrative literature review will critically examine and summarize the existing data. Particular attention is paid to the biological processes, clinical signs and symptoms, treatment advances, and suggestions for customized dental care. Optimizing care and results for this particular patient population requires an understanding of the relationship between endodontic disease and systemic immune dysfunction.